Economic considerations for bariatric surgery and morbid obesity - Eldo E Frezza; Mitchell Wacthell; Bradley Ewing (Dove Medical Press, 2009)
Eldo E Frezza, Mitchell Wacthell1, Bradley Ewing21Center for Metabolic Disease and Texas Tech University, Department of Pathology, 2Rawls Business School, Texas Tech University, Lubbock, TX, USAAbstract: The obesity epidemic is also an economic tragedy. This analysis evaluates the economic effects and the potential to improve the well-being of both individual and societal wealth. Econometric techniques should carefully assess the degree to which obesity affects declines in business output, employment, income, and tax revenues at the regional and national levels. Microeconomics assesses lost productivity and associated wages and profit. Macroeconomics assesses trends associated with employment, inflation, interest rates, money supply, and output. To decrease the adverse economic consequences of the obesity epidemic, policy makers must emphasize bariatric surgery as a cost-effective option for qualified patients. Early intervention, education, and tax rebates for obese individuals who undergo bariatric surgery and for medical centers and doctors would likely have positive economic effects on the whole economy in a few years.Keywords: bariatric surgery, morbid obesity, economics